2016
DOI: 10.1063/1.4967778
|View full text |Cite
|
Sign up to set email alerts
|

Li(Zn,Co,Mn)As: A bulk form diluted magnetic semiconductor with Co and Mn co-doping at Zn sites

Abstract: We report the synthesis and characterization of a series of bulk forms of diluted magnetic semiconductors Li(Zn1-x-yCoxMny)As with a crystal structure close to that of III-V diluted magnetic semiconductor (Ga,Mn)As. No ferromagnetic order occurs with single (Zn,Co) or (Zn, Mn) substitution in the parent compound LiZnAs. Only with co-doped Co and Mn ferromagnetic ordering can occur at the Curie temperature ∼40 K. The maximum saturation moment of the this system reached to 2.17μB/Mn, which is comparable to that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 39 publications
1
10
0
1
Order By: Relevance
“…We measured magnetotransport down to 5 K and observed large intrinsic negative magnetoresistance (nMR) of up to ~40%, almost 10 times greater than the magnetoresistance in typical metallic magnetic materials [26][27][28][29] (< 5%) and more than twice that of the magnetoresistance values in many dilute magnetic semiconductors (~15%). [30,31] Magnetic measurements on single crystals confirm the previously reported magnetic structure: the emergence of an A-type antiferromagnetic (AF) phase below TN = 132 ± 1 K consisting of ferromagnetic (FM) layers, with an in-plane magnetic easy axis along the crystallographic baxis, coupled antiferromagnetically along the c-axis (Figure 1A,B). [25] The magnetic structure of CrSBr, coupled with its easily cleavable layered vdW structure, high magnetic ordering temperature, and strong coupling between magnetism and transport make this compound attractive to advance the fields of magnetic semiconductors, 2D magnetism, and nanospintronics.…”
Section: Main Textsupporting
confidence: 85%
See 1 more Smart Citation
“…We measured magnetotransport down to 5 K and observed large intrinsic negative magnetoresistance (nMR) of up to ~40%, almost 10 times greater than the magnetoresistance in typical metallic magnetic materials [26][27][28][29] (< 5%) and more than twice that of the magnetoresistance values in many dilute magnetic semiconductors (~15%). [30,31] Magnetic measurements on single crystals confirm the previously reported magnetic structure: the emergence of an A-type antiferromagnetic (AF) phase below TN = 132 ± 1 K consisting of ferromagnetic (FM) layers, with an in-plane magnetic easy axis along the crystallographic baxis, coupled antiferromagnetically along the c-axis (Figure 1A,B). [25] The magnetic structure of CrSBr, coupled with its easily cleavable layered vdW structure, high magnetic ordering temperature, and strong coupling between magnetism and transport make this compound attractive to advance the fields of magnetic semiconductors, 2D magnetism, and nanospintronics.…”
Section: Main Textsupporting
confidence: 85%
“…Such giant intrinsic fixed-field MRR is nearly 10 times larger than typical magnetic metals [26][27][28][29] and double that of many dilute magnetic semiconductors. [30,31] Above TN, the fixed-field MRR is non-zero and negative, manifesting a local minimum between 150 and 170 K. This temperature range is consistent with the Weiss constants extracted from the magnetic susceptibility data (θCW = 185, 164 and 184 K for the a-, b-, and c-axes, respectively) (Table S2) and signals the emergence of a hidden magnetic phase above TN characterized by ferromagnetically ordered layers, with no long range magnetic order between the layers. [42] In summary, we demonstrate CrSBr to be a robust antiferromagnetic semiconductor with exceptionally strong coupling between magnetic and electronic properties manifested through the observation of nMR up to ~40%.…”
Section: Main Textmentioning
confidence: 99%
“…the "111" type Li(Zn,Mn)As、 "122" type (Ba,K)(Zn,Mn) 2 As 2 and "1111" type (La,Ca)(Zn,Mn)SbO, which are named by the chemical ratio of their parent phases. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] Among these new DMSs, the ThCr 2 Si 2 type (Ba,K)(Zn,Mn) 2 As 2 has a Curie temperature (Tc) up to 230 K which marks the current reliable record Tc for DMSs where ferromagnetism is mediated by carriers. [12][13] The (Ba,K)(Zn,Mn) 2 As 2 is believed to be one of milestone materials for the research of DMSs.…”
Section: Introductionmentioning
confidence: 99%
“…We present our data on PF and doping levels in light of experimental evidence on few LiZnX systems. Recently, polycrystalline samples of LiZn 1−x As were successfully synthesized with less than 15 % doping by solid-state re-action [51]. The DTA measurements have shown that the melting temperature of LiZnP [13] and LiZnAs [14] are 850 and 950 0 C, respectively.…”
Section: Transport Propertiesmentioning
confidence: 99%